Politics, finance and the role of economics : an essay on the control of public enterprise - Foster, Christopher D. (London : Allen and Unwin, 1971)
This book is about what differences could the common market make to the relation between government and public enterprise.
Includes bibliographical references and index.
oo 09/08/2018
Loans
Keywords: Government business enterprises